Efforts to Improve Student Learning Outcomes on the Subject I Obey the Rules Through a Lecture Model on Students at MIS Al Ansori - Farhunnissa , Farha; Marisa, Eti (MANDAILING GLOBAL EDUKASIA, 2024)
This research aims to improve student learning outcomes in learning Islamic religious education by using the ceramah model. This research is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this research are primary school madrasah students. The data of this research was obtained with test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze the learning activities of teachers and students. The data analysis technique used in this research is descriptive statistics by comparing the results obtained with research success indicators. The research results show that the lecture model can improve student learning outcomes in learning Islamic religious education. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 45.01%, the first cycle 79.39% and in the second cycle it increased to 90.16%. Thus, the use of the lecture model can be used as an alternative to improve student learning outcomes in Islamic religious education.